Sensory and physical properties of Pla-duk-ra (Dried Fermented Catfish) at different conditions of drying - Siti Azhani; Hniman, Adilan; Laehmad, Nattaya; Hanifarianty, Sherly; Masniyom, Payap; Masniyom, Tawat Noipom; Wae-hayee, Makatar (Insight, 2018)
In southernmost Thailand, big scale production of catfish demands a development of new lines of catfish-based products to fully utilize the raw material. Pla-duk-ra (dried fermented catfish) is one such innovation. Traditional method of sunlight drying is commonly used to dry Pla-duk-ra. However, products are highly prone to contamination since they are dried in exposed area. Direct exposure to sunlight could also affect heat labile and light-sensitive nutrients. In this study, other methods of drying were investigated to dry Pla-duk-ra with improved hygiene practice, physical properties and sensory profile. Two scenarios were studied in this work. The objective of the first scenario was to determine the best range of temperature to dry a good and acceptable Pla-duk-ra by comparing open sun drying (range 40˚C to 50˚C) and shade drying (under the roof; 30˚C to 40˚C) . The best range of temperature obtained was then used for the second scenario where open sun, infrared and tray drying were further studied. Moisture content, water activity, colour, texture profile analysis were performed on the Pla-duk-ra samples. Fried Pla-duk-ra was used in sensory evaluation to investigate consumer’s acceptance and preference. Open sun drying was found to be more superior to dry Pla-duk-ra resulting in darker shade of product as compared to shade drying. The moisture content for open sun drying and shade drying of Pladuk-ra were reported 23.65% and 28.06%, respectively. Infrared heater gave the highest water activity (0.77) with the highest score for redness. Meanwhile, Pla-duk-ra dried under the hot-air tray resulted in the highest score for brightness (L*). Overall acceptance by the consumer showed that the Pla-duk-ra dried under the hot-air tray was the most preferred followed by open sun drying and infrared heater drying. To this end, hot-air tray drying could be applied in drying Pla-duk-ra in large scale production.